Salute to Marie-Josée - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Photo: D.R. Marie-Josée Jehl, who is known personally to a great many Spore readers, is leaving CTA after more than eleven years service. She joined the Centre in 1988 from the Council of Europe in Strasbourg, and worked first as assistant...